2021
DOI: 10.1101/2021.03.09.434685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trophic transfer of microplastics enhances plastic additive accumulation in fish

Abstract: A variety of chemical additives are incorporated into plastics during their production process to give desirable properties. Although studies have suggested that microplastic ingestion can lead to accumulation of these chemicals in marine organisms, none provided the direct evidence in fish species. Here, we demonstrated the tissue accumulation of chemical additives in fish following microplastic ingestion. We exposed fish (Myoxocephalus brandti) to polyethylene microplastics compounded with brominated flame r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…In another study, UV326, UV328, and UV329 were found at concentrations ranging from 1.34 to 45.6 ng g −1 (dry weight, dw) on Gran Canaria Island (Spain) [ 50 ]. Hasegawa et al recently showed similar accumulation patterns between direct ingestion from the water column and indirect exposure via the trophic transfer pathway for UV327 in marine fish [ 51 ]. In a recent monitoring study, the sum of nine benzotriazole UV stabilizers (including the five target chemicals in this study) were found in river water (17.0–32.5 ng L −1 ) and sediment (2.0–22.6 ng g −1 , dw) in Korea [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, UV326, UV328, and UV329 were found at concentrations ranging from 1.34 to 45.6 ng g −1 (dry weight, dw) on Gran Canaria Island (Spain) [ 50 ]. Hasegawa et al recently showed similar accumulation patterns between direct ingestion from the water column and indirect exposure via the trophic transfer pathway for UV327 in marine fish [ 51 ]. In a recent monitoring study, the sum of nine benzotriazole UV stabilizers (including the five target chemicals in this study) were found in river water (17.0–32.5 ng L −1 ) and sediment (2.0–22.6 ng g −1 , dw) in Korea [ 52 ].…”
Section: Discussionmentioning
confidence: 99%